The Violence of Hiroshima: Hersey, Bataille and Caruth - Jocelyn Dupont (Sillages Critiques, 2017)
This article deals first with John Hersey’s 1946 Hiroshima, one of the earliest literary responses in English to the nuclear bombing of the city of Hiroshima in August 1945 and one of the most destructive acts of military violence in the 20th century. It then focuses on French philosopher’s Georges Bataille’s singular and disquieting review of Hersey’s short book, published the following year in Critique. Finally, it discusses the somewhat unexpected return of Bataille’s text in Cathy Caruth’s 1995 seminal collection Trauma: Explorations in Memory, and endeavors to assess Bataille’s contemporary relevance to trauma studies. It appears that these three texts operate a process of traumatic transmission and literary actualization of the catastrophe.